EFL students’ use of AI as collaborative learning tools: Practices and perspectives - Sefti Novalia Putri; Sinarman Jaya (English Learning Innovation, 2026)
Artificial intelligence is becoming widely used by students in their learning. However, limited research has examined how Indonesian EFL students perceive and use AI as collaborative partners in their academic tasks. This study investigated students’ digital mindsets, practices, and reflections on the pedagogical and ethical dimensions of AI use. It was conducted in four universities in Bengkulu, Indonesia, with 160 student participants enrolled in EFL programs. A mixed-methods design was employed by combining survey data with semi-structured interviews, which allowed the study to capture both the breadth of students’ digital engagement and the depth of their individual experiences. Descriptive statistics and thematic analysis were applied to examine the quantitative and qualitative data sets, enabling triangulation of findings. The results reveal moderately positive digital mindsets, as reflected in the mean scores indicating openness and perceived usefulness of AI tools for idea generation, text drafting, and linguistic enhancement. Qualitative data revealed that students viewed AI as a supportive partner that develops creativity, peer-like feedback, and collaborative problem-solving. At the same time, concerns about accuracy, ethical responsibility, and dependency highlighted the need for careful and responsible integration. AI tools function not only as supplementary aids but as collaborative agents that mediate cognitive and social dimensions of learning. The findings extend current discussions in the Technology Acceptance Model, socio-cultural theory, and self-regulated learning by demonstrating that AI can enhance individual reasoning and facilitate students' learning more effectively.